Impact of expanded strong opioid availability on opioid prescription patterns in patients with cancer: A population-wide cohort study in Taiwan - Tsung-Che Wu; Chih-Hung Hsu; Wei-Zen Sun; Ho-Min Chen; Chih-Peng Lin; Yu-Yun Shao (Elsevier, 2021)
Background One of the major barriers to adequate cancer pain management in Taiwan is the limited prescription options regarding strong opioids. Internationally recommended strong opioids, including oxycodone and hydromorphone, were not introduced in Taiwan until late 2014. We analysed the patterns in opioid prescription for cancer pain management, after the introduction of new opioid options.Methods All inpatient and outpatient clinical visits from January 1, 2012, to December 31, 2017, with the diagnosis of cancer and the analgesic prescriptions were collected from the database of National Health Insurance, Taiwan, and analysed. Opioids were grouped into strong opioids, weak opioids, and guideline non-recommended opioids.Findings A total of 1, 292, 905 patients with cancers were included. Approximately 50% of patients used analgesics, 50% of which were opioids; the proportions were stable during the study period. The annual cumulative opioid use per patient (defined daily dose, DDD) significantly decreased from 36•41±102•59 (Mean±SD) in 2012 to 32•42±100•99 in 2017 (p < •001). The annual cumulative strong opioid use per patient increased significantly from 17•54±89•23 in 2012 to 19•28±94•97 in 2017 (+9•90%, p < •001). In parallel, the annual cumulative weak opioids use per patient decreased from 18•64±40•81 in 2012 to 13•04±26•79 in 2017 (−30•04%, p < •001). Among extended-release strong opioids, the use of transdermal fentanyl significantly decreased after oxycodone and hydromorphone were introduced (p < •001).Interpretation Increased therapeutic options in strong opioid prescriptions led opioid prescription patterns to evolve towards international cancer pain management guidelines. In addition, increased accessibility to a wider range of different strong opioids may facilitate more efficient opioid titration and rotation - and thus decrease, not increase, the opioid usage.Funding This study was supported by Ministry of Science and Technology, Taiwan (MOST-106-2314-B-002-213 and MOST-108-2314-B-002-072-MY3), Ministry of Health and Welfare, Taiwan (MOHW109-TDU-B-211-114002), National Taiwan University Hospital, Taipei, Taiwan (NTUH-103-002314 and NTUH. 105‐S2954), and National Center of Excellence for Clinical Trial & Research, National Taiwan University Hospital, Taipei, Taiwan (NCTRC201208 and NCTRC201603).